The Loss of Boredom and the End of the Human. Issue 3 (December 2015) - Gere, Charlie
Abstract : This paper looks at the role of boredom as central to the emergence of the human, and at its disappearance in our hypermediated culture. It does so through the works of Giorgio Agamben, in particular his discussions of the apparatus and of Stimmung, mood; his engagement with Heidegger's notion of boredom as Stimmung ; and Agamben's radical reading of Aristotle's understanding of potentiality. Finally through a consideration of the relation between Agamben and John Cage and other avant-garde artists working with the idea of boredom, this paper examines the role of art in allowing boredom to reveal the fundamental inoperativity of the human, something that the culture of contemporary distraction and hypermediation disavows.